2002
DOI: 10.1063/1.1426236
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel-magnetoresistance system with an amorphous detection layer

Abstract: We have studied magnetic tunnel junctions using an amorphous CoFeNiSiB soft magnetic layer. At room temperature a tunnel-magnetoresistance ratio of 12% was achieved with a switching field of the amorphous layer of 12 Oe. The effect could be enhanced up to 22% by annealing. Investigations on single amorphous layers show a thermal stability up to 350 °C annealing temperature even for very thin layers. Due to the special preparation technique, an in-plane anisotropy is induced resulting from an oblique-incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The reference layer usually is an artificial ferrimagnet (AFi) exchange biased by a natural antiferromagnet like PtMn or IrMn. For the soft electrode, mostly NiFe has been used (4) and only recently this has been substituted by amorphous alloys of 3d ferromagnets with metalloids like B or Si, showing both, low switching fields (5) and also high tunnel magnetoresistance (TMR) (6; 7).…”
Section: Introductionmentioning
confidence: 99%
“…The reference layer usually is an artificial ferrimagnet (AFi) exchange biased by a natural antiferromagnet like PtMn or IrMn. For the soft electrode, mostly NiFe has been used (4) and only recently this has been substituted by amorphous alloys of 3d ferromagnets with metalloids like B or Si, showing both, low switching fields (5) and also high tunnel magnetoresistance (TMR) (6; 7).…”
Section: Introductionmentioning
confidence: 99%
“…Wang [9] demonstrated high tunnelling magnetoresistance (TMR) ratio (70%) and low H sw (6 Oe) from the optimized Co 60 Fe 20 B 20 -MTJ structure but the resistance-area product (RA) was too high (24 MOmm 2 ). Ka¨ufler et al [10] introduced Co 64 Fe 5 Ni 5 Si 13 B 13 free layer MTJ that showed H sw of 12 Oe with possibility to achieve high thermal stability. Lately, Chun et al [11] and Hwang et al [12] have introduced amorphous Ni 16 Fe 62 Si 8 B 14 and Co 70.5 Fe 4.5 Si 15 B 10 MTJs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in barrier quality, such as removal of pinholes and fewer impurities, and metal/barrier interfaces results in the enhancement of the TMR values [3][4][5][6][7][8] with a maximum of 70% reported for Alumina barriers [7]. In particular, the use of amorphous ferromagnets [9], mainly consisting of alloys of 3D FM with metalloids like Si or B, such as CoFeB, could reduce the interface roughness, and allow the growth of Al films, continuous, down to 0.4 nm thick. The correlation between the smoothness or sharpness of the electrode/barrier interface and a high TMR was reported by several groups [10] and observed by electron microscopy of CoFeB/AlO x interfaces [11].…”
Section: Introductionmentioning
confidence: 99%